The Importance of Education and Trust Building for Wabanaki Self-Governance - Tomer, Katie (Maine Policy Review, 2021)
Education and trust building are inextricably intertwined parts of addressing failed efforts of the state of Maine and the Wabanaki tribes to resolve tribal self-governance issues. Lack of structural and financial support for the delivery of Wabanaki Studies Law content directly affects tribal-state relations and Wabanaki self-determination in Maine. This article examines legislative proposals, current laws, and scholarly research and explore how they relate to tribal self-governance. Maine needs strategies for trust building and increased educational experiences for all Maine residents about Wabanaki people and ways of knowing.
Keywords: Wabanaki Studies Law; Maine Indian Land Claims Settlement Act; tribal sovereignty